2000
DOI: 10.1007/s002590000317
|View full text |Cite
|
Sign up to set email alerts
|

Indium-111 labelled white blood cell scintigraphy in cranial and spinal septic lesions

Abstract: Cranial and spinal infections are severe events that require timely diagnosis and treatment. Physical and neurological examination, laboratory tests and radiological imaging may be insufficient for assessing cranial and spinal septic lesions. This study aimed to evaluate the accuracy of indium-111 white blood cell (WBC) scan in assessing the presence of leucocytes in intracranial and spinal lesions, and in the diagnosis, management and follow-up of primary, post-traumatic and post-surgical infections. One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…9 These authors further pointed out that 1 month of treatment led to normalization of the indium scan, a result that is not inconsistent with the work of Datz and Thorne. 10 The radionuclide (indium)-labeled leukocyte scan Two studies 11,12 have claimed that indium scan is 100% sensitive; one of these also found the study to be 100% specific. 12 Our results bring such reports into question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 These authors further pointed out that 1 month of treatment led to normalization of the indium scan, a result that is not inconsistent with the work of Datz and Thorne. 10 The radionuclide (indium)-labeled leukocyte scan Two studies 11,12 have claimed that indium scan is 100% sensitive; one of these also found the study to be 100% specific. 12 Our results bring such reports into question.…”
Section: Discussionmentioning
confidence: 99%
“…10 The radionuclide (indium)-labeled leukocyte scan Two studies 11,12 have claimed that indium scan is 100% sensitive; one of these also found the study to be 100% specific. 12 Our results bring such reports into question.…”
Section: Discussionmentioning
confidence: 99%